2019
DOI: 10.1136/bcr-2018-228741
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough and cystic lung disease caused byBordetella bronchisepticain a patient with AIDS

Abstract: A 24-year-old man with a history of HIV and large B cell lymphoma (currently in remission) presented with fever, dry cough and dizziness. His CD4+ count was undetectable, and the HIV viral load was 109 295 cop/mL. Physical examination revealed fever, hypotension and tachycardia with coarse breath sounds in the middle and lower chest zones bilaterally. Chest imaging showed diffuse abnormal micronodular and patchy infiltrates, without focal consolidation. A cavitary lesion was noted measuring 5×2 cm in axial dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While we acknowledge the possibility that B. bronchiseptica may have represented airway colonization in our patient, her immunosuppressed status and clinical presentation suggest that it played a pathogenic role. For example, our patient’s chronic cough began approximately a month before she developed shortness of breath, an important consideration given that chronic cough has been previously associated with human B. bronchiseptica infections [ 11 , 12 ]. Additionally, our case represents at least the second patient diagnosed with B. bronchiseptica pneumonia while receiving nivolumab [ 13 ] and the fourth documented patient co-infected with COVID-19 and B. bronchiseptica [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we acknowledge the possibility that B. bronchiseptica may have represented airway colonization in our patient, her immunosuppressed status and clinical presentation suggest that it played a pathogenic role. For example, our patient’s chronic cough began approximately a month before she developed shortness of breath, an important consideration given that chronic cough has been previously associated with human B. bronchiseptica infections [ 11 , 12 ]. Additionally, our case represents at least the second patient diagnosed with B. bronchiseptica pneumonia while receiving nivolumab [ 13 ] and the fourth documented patient co-infected with COVID-19 and B. bronchiseptica [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested bacterial colony counts greater than 10 4 CFU/mL in bronchoalveolar lavage fluid could differentiate colonization of the respiratory epithelium from infection. [21] However, since B bronchiseptica is rarely isolated and clearly has pathogenic potential, this threshold should be used cautiously in immunocompromised patients with compatible clinical syndromes. In our clinical microbiology laboratory, B pertussis, B parapertussis, and B bronchiseptica are initially identified as a Bordetella group by MALDI then supplementary tests such as biochemical and growth characteristics are used to specify B bronchiseptica.…”
Section: Discussionmentioning
confidence: 99%
“…B bronchiseptica is typically diagnosed via culture of respiratory tract secretions and blood as a Gram negative coccobacillus that will grow on standard media such as sheep blood and chocolate agar. Some authors have suggested bacterial colony counts greater than 10 4 CFU/mL in bronchoalveolar lavage fluid could differentiate colonization of the respiratory epithelium from infection [21] . However, since B bronchiseptica is rarely isolated and clearly has pathogenic potential, this threshold should be used cautiously in immunocompromised patients with compatible clinical syndromes.…”
Section: Discussionmentioning
confidence: 99%